Rectal Cancer Presenting with Isolated Thyroid Metastasis: A Case Report - Karan Sood; Pratiksha Tyagi; Amol Dongre (Journal of Clinical and Diagnostic Research)
A 59-year-old female with chief complaints of white discharge per rectum for one month, pain in the lower abdomen for one month, and neck swelling for six months. She was diagnosed with adenocarcinoma of the rectum with a single site of metastases in the right lobe of the thyroid. The patient was given six months of FOLFOX, following which the rectal primary showed a complete response but stable disease in the thyroid lesion. The patient underwent a thyroidectomy, which confirmed a metastasis from the rectum. She was given radiation to the thyroid bed postoperatively and underwent chemoradiation for the rectal primary. She underwent a wait-and-watch approach and is disease free for two years. Thyroid metastases from Colorectal Carcinoma (CRC) are an uncommon clinical finding, accounting for 2-3% of all malignant tumors of the thyroid. The reported incidence in CRC patients is approximately 0.1%, with most cases involving extensive disease and poor prognosis. In the available literature, only 24 cases of thyroid gland metastases from CRC are reported. However, isolated metastases to the thyroid have been observed, raising diagnostic and therapeutic challenges. Fine-needle aspiration cytology and Immunohistochemistry (IHC), using markers such as Thyroid Transcription Factor-1 (TTF-1), Thyroglobulin (Tg), and CDX2, play pivotal roles in confirming the diagnosis. Advances in imaging, particularly Positron Emission Tomography (PET) scans, have improved detection rates. The vascular and lymphatic systems facilitate metastatic spread, yet the role of thyroidectomy remains controversial due to a lack of survival benefits. Chemotherapy and radiotherapy are typically reserved for palliation in cases of advanced disease.